2003
DOI: 10.1046/j.1523-1755.2003.00824.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-induced fibronectin and collagen type III expression in renal fibroblasts can occur independent of TGF-β1

Abstract: These data show that in renal fibroblasts exposure to high glucose can increase matrix production independent of endogenous TGF-beta1. Although glucose activation is accompanied by an increased production of latent TGF-beta1, which can have an important role in vivo, the data suggest involvement of alternative growth factors in the mechanism by which hyperglycemic conditions can modulate matrix accumulation in diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 42 publications
4
28
0
Order By: Relevance
“…In addition, TK173-⌬T␤RII was exposed to either TGF-␤1 or high glucose. We recently demonstrated that glucose-induced collagen type III was not affected in these transfected cells (8). Now we also show that collagen type I secretion induced by high glucose was not affected in TK173-⌬T␤RII, whereas the effect of TGF-␤1 was completely abolished (Fig.…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…In addition, TK173-⌬T␤RII was exposed to either TGF-␤1 or high glucose. We recently demonstrated that glucose-induced collagen type III was not affected in these transfected cells (8). Now we also show that collagen type I secretion induced by high glucose was not affected in TK173-⌬T␤RII, whereas the effect of TGF-␤1 was completely abolished (Fig.…”
Section: Resultssupporting
confidence: 67%
“…Recently, we demonstrated a TGF-␤1-independent mechanism of fibronectin and collagen type III upregulation in human renal fibroblasts by high glucose, in a process that might involve alternative growth factors (8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations